Evolutionary Computation - Alavi, Amir; Wang, Gai-Ge (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Computational intelligence is a general term for a class of algorithms designed by nature's wisdom and human intelligence. Computer scientists have proposed many computational intelligence algorithms with heuristic features. These algorithms either mimic the evolutionary processes of the biological world, mimic the physiological structure and bodily functions of the organism,